1997
DOI: 10.1063/1.1148017
|View full text |Cite
|
Sign up to set email alerts
|

New high luminosity “double toroidal” electron spectrometer

Abstract: In this article we describe the design and the operation of an original, high transmission, electrostatic “double toroidal” electron energy analyzer. The double toroidal analyzer allows the high resolution and high luminosity simultaneous measurement of the kinetic energy, and angular distribution of electrons, using a two-dimensional position sensitive detector. The exact shape of the electrodes is deduced from both analytical and numerical electron trajectory calculations. The electron detector is based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 12 publications
0
38
0
1
Order By: Relevance
“…However, after implementing all the above trials, we found it extremely difficult to reach a unique simulation-based solution for the lens table. This could be due to two reasons: (1) With the downhill simplex method implemented in SIMION, it could happen that the numerical optimization ends before the global extremum is found, when the downhill walking step of the multidimensional algorithm is fractionally smaller than the tolerance, thus a single step fools the convergence criteria. (2) With the annealing technique used, the optimization performs efficiently when only a few neighboring points in the lens table are involved.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, after implementing all the above trials, we found it extremely difficult to reach a unique simulation-based solution for the lens table. This could be due to two reasons: (1) With the downhill simplex method implemented in SIMION, it could happen that the numerical optimization ends before the global extremum is found, when the downhill walking step of the multidimensional algorithm is fractionally smaller than the tolerance, thus a single step fools the convergence criteria. (2) With the annealing technique used, the optimization performs efficiently when only a few neighboring points in the lens table are involved.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…1. A new conical lens, with smaller aberrations and an easier alignment procedure, has been designed 2 to replace the original lens.…”
Section: Instrumental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Using electrode geometries derived from this procedure and which slightly deviate from toroidal symmetry, they showed that improved focusing can be achieved, not only for particles traveling in circular trajectories along a centrally located equipotential line, but also for particles of greater or smaller energy than the mean pass energy. Miron et al 11 adopted this approach to develop a high-resolution electron analyzer based on two juxtaposed pairs of modified-toroidal-sector deflector plates possessing noncircular cross section. In the present design, however, our large c parameter value of 2.43 ͑see Sec.…”
Section: ͑3͒mentioning
confidence: 99%
“…8,9 More recently, third generation spectrometers have been developed whose analyzers incorporate two-dimensional positionsensitive detectors, enabling a range of emission angles and energies to be measured in parallel. [10][11][12][13][14][15][16] From the measured arrival positions of electrons at the detectors, their energies and emission angles are deduced.…”
Section: Introductionmentioning
confidence: 99%